How Not to Read Literature: The Nazis’ Appropriation of The Merchant of Venice - William W White (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2020)
In his essay “Reading Law, Reading Literature: Law as Language,” legal scholar James Boyd White extols the interpretive flexibility of literary and legal texts and warns against viewing literature as having “objective and determinate meanings.” White’s warning raises the question of whether a literary work's meaning can be used to promote a morally corrupt agenda. This paper seeks to explore the danger of reducing a work of literature's meaning to a determinate claim by focusing on how Shakespeare’s The Merchant of Venice was utilized by the Nazis as anti-Semitic political propaganda. Shakespeare’s play experienced a massive surge in popularity during Nazi rule, quickly becoming one of the most performed plays during a time when most literary and dramatic works were repressed. The play was promoted as demonstrating Jewish inferiority through its central antagonist, Shylock, whose avaricious and vengeful behavior was viewed as emblematic of the Jewish race’s wickedness. The Reichsdramaturgie, Germany’s theatre branch under Joseph Goebbels’s Ministry of Propaganda, created a heavily edited version of The Merchant of Venice that attempted to destroy the play’s complex handling of Jewish identity. This chiefly concerned altering Shylock’s Jewish daughter Jessica, whose marriage to a Christian would be forbidden under the Nuremberg Laws, to his Aryan foster child. Lines meant to evoke sympathy for Shylock were cut, most notably his famous “Hath not a Jew eyes?” monologue. Nazi-directed stage productions stereotyped Shylock even further, most notably during a notoriously Anti-Semitic production at Vienna's Burgtheater in 1943. This paper’s exploration of The Merchant of Venice's propogandization by the Nazi Party strives to demonstrate that reducing a work of literature to welding a set legal or political message threatens to destroy the complexity of its characters and potentially normalize harmful social prejudices.
Keywords: Shakespeare; Nazis; WWII; Holocaust